Association of Periapical Status of Endodontically Treated Teeth with Restoration and Root Canal Filling Quality - N Roghanizad; N Omatali; AA Moshari; M Sadaghiani; M Kalantari (Islamic Azad University, 2019)
Background and Aim: The main goal of root canal treatment is to prevent or treat apical periodontitis. The aim of the present study was to assess the coronal restoration status, root canal filling quality, periapical health condition, and related factors in endodontically treated teeth at the Dental Faculty of Islamic Azad University of Medical Sciences, Tehran, Iran, in 2011-12. Materials and Methods: In this descriptive, historical cohort study, a total of 160 teeth submitted to endodontic treatment were clinically and radiographically reexamined one year (minimum) postoperatively. Each volunteer answered a questionnaire on demographic and socioeconomic factors. They were also questioned about the factors related to endodontic and restorative treatments. The restoration and root canal filling quality was classified according to the modified criteria introduced by Tronstad et al. The periapical status was evaluated according to the periapical index (PAI) scores. Results: Periapical lesions (diseased/failure) were most prevalent in Inadequate Restoration/Inadequate Root Canal Filling group (70%) followed respectively by Inadequate Restoration/Adequate Root Canal Filling group (52.2%), Adequate Restoration/Inadequate Root Canal Filling group (30%), and Adequate Root Canal Filling/Adequate Restoration group (15.5%). Conclusion: According to the results, an efficient appointment scheduling system has the greatest impact on the completion of coronal restoration after endodontic treatments. Provision of adequate root canal filling and perfect coronal restoration can reduce the prevalence of postoperative periapical lesions and increase the success rate of endodontic treatments.